Market Supervision in the European Union : Integrated Administration in Constitutional Context - Cleynenbreugel, Pieter van (Nijhoff studies in EU law, 2015)
In Market Supervision in the European Union, Pieter Van Cleynenbreugel compares the emergence of divergently structured supranational market supervision mechanisms in six different sectors of EU regulation and identifies common or converging constitutional benchmarks underlying those sector-specific administrative design developments.